PEMANFAATAN EKSTRAK DAUN KANGKUNG (Ipomea aquatica Forssk) DALAM PEMBUATAN SHAMPO - Yuliani, Yesi; Nabil Irfanurhalim, Muhammad; Abdullah Wadyapta Rhamadhani, Rizqi (SMA Trensains Muhammadiyah Sragen, 2023)
Abstract Dandruff is a problem on the scalp. The symptoms of dandruff are fine white granules or flakes in the hair and scalp which are white or grayish in color and sometimes oily. Apart from that, dandruff is usually accompanied by an itchy feeling on the scalp. Kale has properties to prevent scalp and has a complete nutritional content, including protein, fat, carbohydrates, fiber, calcium, phosphorus, iron, vitamin A, vitamin B1, vitamin C, water. Making this shampoo aims to make people more practical in using shampoo made from herbal plants. Shampoos that have been circulating are usually made of chemicals that have side effects that are quite dangerous. The way to make shampoo is to boil it in water for a few minutes and then filter it and cool it in the refrigerator. After it cools, the boiled water will be mixed with the ingredients for making shampoo.